New and little-known Isotominae (Collembola, Isotomidae) from South Africa - Janion-Scheepers, Charlene; Potapov, Mikhail; Deharveng, Louis (Zootaxa, 2023)
Three new species, Parisotoma ruseki sp. nov., P. yehlathi sp. nov., and Folsomotoma amyliuae sp. nov. are described from South Africa. Parisotoma ruseki sp. nov. is characterized by four posterior s-chaetae on each side of the three first abdominal segments and seven posterior chaetae on dens, Parisotoma yehlathi sp. nov. by five s-chaetae and eight chaetae on dens, respectively. All s-chaetae on the body of Folsomotoma amyliuae sp. nov. are short, unlike its congeners. The genera Folsomotoma and Halisotoma are recorded for the first time in South Africa.